Al Futuhat al Ilahiyyah bitawdih tafsir al Jalilayn li daqaiq al khafiyyah - Al_Jamal (Matba'ah Isa al baby al Halabi)
ws.jl.1. c.1-3 , Jl.3,4.c.1-4 jl.2,4.c.1-5/stoc4=jil. 1,c.1-3; jil.2-3, c.1-4; jil.4=c.1-2